Iowa spring bird report, Babs & Loren Padelford, spring 1999 - Padelford, Babset al; Padelford, Lorenet al (1999)
An annotated list of birds sighted by Babs and Loren Padelford. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1999. Epson - sheet feed